La esperanza del cuadrado medio (2007)
ABSTRACT: Expectation of the square mean is fundamental in the analysis of variance in order to establish the F test adapted in the contrast of factors arranged in the diagram of structure under a model of experimental classification chosen by the researcher. The lack of knowledge of the mean square is being blind at the time of interpretation of results, because the misunderstanding of such a component can give inappropriate conclusions which in turn get bias in statistic analysis-base decisions. To construct the mean square it is necessary to previously known if the effect is random, fixed or mixed.